Toxicity of neem extracts (Azadirachta indica) to the coffee red mite Oligonychus ilicis - Mourão, Sheila Abreu; Zanuncio, José Cola; Filho, Angelo Pallini; Guedes, Raul Narciso Carvalho; Camargos, Adonai Bruneli de (Pesquisa Agropecuaria Brasileira, 2004)
The objective of this work was to study the toxicity of extracts of oil cake, seeds and leaves of Azadirachta indica A. Juss (neem) to the coffee red mite Oligonychus ilicis (McGregor) (Acari: Tetranychidae). Concentration-mortality and instantaneous rate of populational growth were determined for adult females of the red mite on disks of coffee with 3.5 cm diameter, floating on water and impregnated with dry residues of the neem extracts. Concentrations of these extracts which caused 50% mortality of the individuals of O. ilicis were 0.02, 15.9 and 121.4 mg/mL; while 99% mortality of this mite was reached with 10.9, 520.9 and 277.4 mg/mL for oil cake, seeds and leaves extracts, respectively. The instantaneous rate of populational growth of O. ilicis dropped as the extract doses increased up to 0.075, 15 and 144 mg/mL for oil cake, seeds and leaves extracts, respectively